2021
DOI: 10.1073/pnas.2013056118
|View full text |Cite
|
Sign up to set email alerts
|

Complexity and graded regulation of neuronal cell-type–specific alternative splicing revealed by single-cell RNA sequencing

Abstract: The enormous cellular diversity in the mammalian brain, which is highly prototypical and organized in a hierarchical manner, is dictated by cell-type–specific gene-regulatory programs at the molecular level. Although prevalent in the brain, the contribution of alternative splicing (AS) to the molecular diversity across neuronal cell types is just starting to emerge. Here, we systematically investigated AS regulation across over 100 transcriptomically defined neuronal types of the adult mouse cortex using deep … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 37 publications
2
51
0
Order By: Relevance
“…Cells in the splicing latent space strongly cluster by cell type (annotated by Yao et al [24] based on gene expression). A similar analysis was recently performed [36] on a different cortex subregion in which most, but not all, neuron subclasses could be distinguished based on splicing profiles (e.g., L6 CT and L6b could not be separated). However, the authors only considered annotated skipped exons, a subset of the events we quantify, and used a different dimensionality reduction technique.…”
Section: Cell-type-specific Splicing Signal Is Strong and Complementary To Gene Expressionmentioning
confidence: 76%
“…Cells in the splicing latent space strongly cluster by cell type (annotated by Yao et al [24] based on gene expression). A similar analysis was recently performed [36] on a different cortex subregion in which most, but not all, neuron subclasses could be distinguished based on splicing profiles (e.g., L6 CT and L6b could not be separated). However, the authors only considered annotated skipped exons, a subset of the events we quantify, and used a different dimensionality reduction technique.…”
Section: Cell-type-specific Splicing Signal Is Strong and Complementary To Gene Expressionmentioning
confidence: 76%
“…Previous studies have shown that genes showing changes in alternative splicing may reflect different biological processes from those with DE. For example, a recent scRNA-seq study in the adult mouse cortex found differences in splicing dynamics across cells were not explained by neuronal cell type definitions based on differences in isoform-agnostic transcript expression levels, suggesting that alternative splicing regulation might be orthogonal to transcriptional regulation in specifying neuronal identity and function (Feng et al 2021). Therefore, differential alternative splicing may complement DE analysis in characterizing gene regulation.…”
Section: Differential Splicing Analysismentioning
confidence: 99%
“…The hippocampus has cell- and compartment-specific transcriptomes, as it is divided into 4 major subregions (CA1, CA2, CA3, and the dentate gyrus) with diverse gene expression schemes to control subregion-specific properties and functions (Masser et al, 2014 ; Cembrowski et al, 2016 ; Farris et al, 2019 ). Several studies have identified alternative splicing programs that readily distinguish neuron cell classes (glutamatergic, GABAergic, glia; Zhang et al, 2014 ; Furlanis et al, 2019 ; Sapkota et al, 2019 ; Feng et al, 2021 ; Joglekar et al, 2021 ) and to a lesser extent distinguish neuron subclasses (CA1, CA3; Furlanis et al, 2019 ; Joglekar et al, 2021 ), indicating that alternate isoform expression is a driver of functional specification (Furlanis et al, 2019 ). Cell-specific expression of transcription factors and epigenetic modifiers likely induce expression of these specialized transcriptomes, but it is still unknown how they communicate with the splicing machinery to induce expression of one isoform over another.…”
Section: Are There Subregion-specific Splicing Programs In the Hippocampus?mentioning
confidence: 99%
“…Alternative isoform expression is regulated by a complex interplay of splicing factors (Fischer et al, 2011 ; Carey and Wickramasinghe, 2018 ), epigenetic modifications (Zhang et al, 2020 ), transcription factors (Thompson et al, 2019 ), enhancers/repressors (Conboy, 2021 ), and RNA binding proteins (Yee et al, 2019 ). Neuron-enriched RBPs, such as RBFOX1 (Jacko et al, 2018 ; Begg et al, 2020 ), ELAVL (Hinman et al, 2013 ; Yokoi et al, 2017 ), NOVA (Jensen et al, 2000 ; Ule et al, 2006 ), and MBNL2 (Wang et al, 2012 , 2015 ; Taliaferro et al, 2016 ), regulate neuronal-specific, or even neuron class-specific (Feng et al, 2021 ), splicing programs by binding to highly conserved sequence motifs in pre-mRNAs and recruiting spliceosome factors to promote or inhibit splicing of specific exons.…”
Section: Introductionmentioning
confidence: 99%